Leaf isoprene and monoterpene emissions vary with fast-slow carbon economics strategies in central Amazon woody species - Robin, Michelle; Gomes Alves, Eliane; Taylor, Tyeen C.; Pinheiro Oliveira, Débora; Duvoisin, Sérgio; Gonçalves, José Francisco C.; Schöngart, Jochen; Wittmann, Florian; Piedade, Maria T. F.; Trumbore, Susan; Schietti, Juliana (Frontiers in Plant Science, 2025)
Plant responses to stress, inter-organismal signaling, and atmospheric chemistry are significantly influenced by leaf volatile isoprenoid (VI) emissions (e.g., isoprene and monoterpenes). Despite their critical roles in ecology and the atmosphere, we have little understanding of whether and how VI emissions vary with axes of plant functional variation. Understanding these relationships is particularly important in tropical forests, which emit more VIs into the atmosphere than any other biome, and where high species diversity necessitates the imputation of plant traits based on functional and evolutionary relationships. Here, we investigated how VI emissions varied with functional trait axes of fast-slow carbon economics strategies (CES) in Central Amazon Forest woody species. We measured leaf-level isoprene and monoterpene emission capacity (Ec; emission measured under standard conditions of photosynthetically active radiation of 1000 µmol m-2 s-1 and leaf temperature of 30 ˚C), and 12 leaf and four stem functional traits for 91 trees from 31 species of angiosperm distributed across different vegetation types: non-flooded upland, white sand, and ancient non-flooded river terrace forests. Principal component analysis (PCA) of functional traits revealed two partially independent main axes of CES: a first axis of leaf strategies and a second of mixed leaf/stem strategies. The capacity to emit monoterpenes was observed in 27 species, and monoterpene emitters occupied the whole range of fast-slow strategies, but magnitudes of monoterpene Ec increased toward faster leaves. The capacity to emit isoprene was observed in 14 species, and isoprene emitters tended to be positioned toward slower leaf/stem strategies, with magnitudes of isoprene Ec also increasing toward slower leaves/stems. Our results highlight the importance of understanding leaf-level emissions to accurately estimate VI fluxes and provide a holistic view of emissions within CES on different organ-system levels. This shows a direction for improving current modeling estimates, which have simplified plant functional type representations and are poorly developed for compounds other than isoprene in the tropics. A more mechanistic representation of plant functional types based on forest functional compositions can reduce modeling emission uncertainties and contribute to understanding the roles of VIs within forest-atmosphere interactions, atmospheric chemistry, and the carbon cycle.